PENERAPAN KONSELING NARATIF UNTUK MENINGKATKAN SELF EFFICACY BELAJAR SISWA DALAM MENGERJAKAN TUGAS - Yusuf, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2021)
The purpose of this study was to determine (1) the description of students' learning self-efficacy in doing assignments before and after the implementation of narrative counseling at SMP Negeri 1 Pangkep (2) The application of narrative counseling can increase students' self-efficacy in doing assignments at SMP Negeri 1 Pangkep. This study used an experimental approach with Pretest-posttest control Group Designs for 24 research samples, which were VIII students at SMP Negeri 1 Pangkep with a classification of 12 experimental groups and 12 control groups, and simple random sampling. This study uses data collection techniques through questionnaires, and observation. Data analysis used descriptive statistical analysis of non parametric Wilcoxon signed ranks test. The results of this study indicate (1) At the time of the pretest, the level of self-efficacy of students in the experimental and control groups was in the low category. However, after being given the treatment of narrative counseling techniques showed a change from a low level of learning self-efficacy to a high category in the experimental group, while for students who were not treated with narrative counseling did not show significant changes or remained in the low category. (2) The application of narrative counseling can increase student learning self-efficacy in doing assignments at SMP Negeri 1 Pangkep